The Trace of Basel within an interdisciplinary research context: forensic handwriting analysis - Ardoino, Diego (Baltistica, 2018)
The Trace of Basel (TB) is generally considered to be the oldest extant text not only in Old Prussian but more generally in a Baltic dialect. According to the traditional point of view  accepted by most scholars (who generally dealt only with the linguistic analysis of the micro text), the date attested in the colophon immediately preceding TB (1369) is also applicable to the micro text itself. A sort of communis opinio also concerns the origin of TB, which would have been inserted in (or in any case connected to) Prague. Furthermore, some scholars base their interpretation of TB on the hypothesis that it was written by the same hand that wrote the colophon and/or the talking drawing around which TB was inserted. All these aspects are questioned by the handwriting examination of TB, which confirms the results of the codicological, palaeographic and philological analysis of the micro text presented in Ardoino 2012a; 2012b; 2013.
Keywords: Old Prussian; the Trace of Basel; Baltic Philology; forensic handwriting analysis